The rights of refugees under international law - Hathaway, James C (Cambridge University, 2013)
This book presents the first comprehensive analysis of the human rights of refugees as set by the UN Refugee Convention. In an era where States are increasingly challenging the logic of simply assimilating refugees to their own citizens, questions are now being raised about whether refugees should be allowed to enjoy freedom of movement, to work, to access public welfare programs, or to be reunited with family members. Doubts have been expressed about the propriety of exempting refugees from visa and other immigration rules, and whether there is a duty to admit refugees at all. Hathaway links the standards of the UN Refugee Convention to key norms of international human rights law, and applies his analysis to the world's most difficult protection challenges. This is a critical resource for advocates, judges, and policymakers. It will also be a pioneering scholarly work for graduate students of international and human rights law.